Periodontal Condition in High-Risk Pregnant Women - Moimaz, Suzely Adas Saliba; Chiba, Fernando Yamamoto; Rodrigues, Fernanda Izaura; Garbin, Cléa Adas Saliba; Saliba, Orlando; Saliba, Nemre Adas (ARCHIVES OF HEALTH INVESTIGATION, 2021)
Introduction: Oral health is related to the systemic health of the pregnant woman and the fetus, highlighting the importance of the oral health approach as a gestational health problem. Objective: To verify the prevalence of periodontal pocket and to analyze the relationship of the condition with sociodemographic factors, medical history, and behavioral profile in high-risk pregnant women. Methods: This cross-sectional, observational and analytical study comprised 800 high-risk pregnant women. Interviews were performed using a structured questionnaire to obtain data on sociodemographic characteristics, medical history and behavioral factors and the periodontal examination was carried out using the Community Periodontal Index (CPI). Statistical analyzes were performed to estimate odds ratio (OR) and 95% confidence interval (CI) between periodontal pocket and variables age group, living area, skin color, housing, marital status, schooling, family income, gestational period, number of children, arterial hypertension, gestational arterial hypertension, diabetes mellitus, gestational diabetes mellitus, smoking habit and alcoholism. Results: Of the total of 800 pregnant women examined, it was observed that 216 (27%) showed periodontal pocket. The condition was associated with age group (35-45 years: OR=2.498; CI=1.297-4.813; p-value=0.006), schooling (≤7 years: OR=1.638; CI=1.017-2.638; p-value=0.042), family income (≤USD 400.00: OR=1.431; CI=1.004-2.041; p-value= 0.048), diabetes (OR= 2.508; CI=1.511-4.163; p-value=0.000) and smoking habit (OR=2.211; CI=1.460-3.348; p-value=0.000). Conclusions: The prevalence of periodontal pocket was high and the factors age, low schooling, low family income, diabetes and smoking habit are related to greater chances of occurrence in high-risk pregnant women.